Seepage control in sand using bioslurry - Yang, Yang (2021)
This paper presents a new method for seepage control in sand using bioslurry, a suspension of CaCO3 crystals formed using a microbial calcium carbonate precipitation process (MICP). The bioslurry can be permeated through sand or deposit on top of a sand layer. The bioslurry contains high urease active bacteria cells and allows further MICP treatment when introducing cementation solution. In this way, the permeability of the bioslurry layer or bioslurry permeated sand layer could be further reduced to the order of 10−9 m/s through another 2–3 numbers of MICP treatment using a cementation solution with an optimum concentration of 1.6 M. Such a low permeability is hardly achievable using the conventional MICP method which would require many more numbers of treatment to reduce the permeability of sand to be below 10−7 m/s. Therefore, the proposed bioslurry method is not only more effective, but also more efficient. The water barrier layer formed using the proposed method is much less affected by wet and dry or temperature change cycles than compacted clay liners. It also allow cracks in the water barrier layer to be repaired if required.